FAILURE TO ACHIEVE DEVELOPMENT IN SPITE OF A SERIES OF REFORMS: WHAT IS WRONG WITH EFL TEACHERS' ENGLISH PROFICIENCY? - Dereje Tadesse Birbirso (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2014)
This study focuses on one of Ethiopia's unfading education policy problems, namely the poor English proficiency of EFL teachers and their students. Qualitative data was collected through unstructured questionnaire and participant observation from twenty-five randomly selected highly experienced EFL schoolteachers and tertiary EFL educators coming from all corners of the country. Relevant archival data were also collected. Besides, four expert informants were also involved as critical consultants for the study. The data was analyzed qualitatively with the reflective and iterative constant comparative method. The results show that for Ethiopian EFL teachers, the problem of the so-called "poor" English proficiency is actually an outcome or a result of poor socio-educational preconditions that inhibited their holistic development as dignified, full-fledged professional citizens. Particularly, meager living conditions, alienating working environments, and a totalitarian policy and practices known as "Cascade Model" are the chief stumbling blocks to their development as fully proficient EFL teachers.